The Optimization Of Flash Sale Voucher For Promotion At Vila Lumbung Hotel, Seminyak-Bali - Satya Wiguna, I Komang Esa Wira; Lukitasari, Rimalinda; Pramesti, Dinar Sukma (Journey : Journal of Tourismpreneurship, Culinary, Hospitality, Convention and Event Management, 2024)
Voucher Flash Sale is a form of marketing strategy carried out by Hotel Vila Lumbung. Unfortunately, the use of Flash Sale vouchers has not been effective because the sales results have not been able to reach the target. The purpose of this study was to develop a promotional strategy through the use of flash sale vouchers at Hotel Vila Lumbung, Seminyak-Badung. The research method used is qualitative by collecting data through interviews, using marketing mix theory and using SWOT analysis techniques. The results of the study reveal strategies that can be carried out including promoting Flash Sale Vouchers at other OTAs such as fave, traveloka, hotelbeds, roiback and others who have collaborated with the hotel; provide free charge rewards for one day using hotel facilities for each internal staff who successfully sells Flash Sale Vouchers; provide a special barcode in the Flash Sale Voucher which can be accessed online or offline; utilizing hotel facilities as a form of benefit to those who promote it, so that this can minimize the use of budget in the promotion process of Flash Sale Vouchers. With this research, it is hoped that Hotel Vila Lumbung Seminyak-Badung can maximize its strategy in promoting Flash Sale Vouchers.